Angular and impact energy dependence of intensity ratio of Kα, β x-rays to underneath bremsstrahlung radiation emitted from 15 to 25 keV electrons incident on a pure thick Cu (Z=29) target. (June 2019) - Singh, Bhupendra; Prajapati, Suman; Singh, B.K.; Shanker, R.
Abstract: We present new results on angular and impact energy dependence of the relative intensity ratios of Kα and Kβ characteristic (CS) x-ray lines to their respective underneath bremsstrahlung (BS) radiation produced from 15-25 keV electrons incident on a thick polycrystalline pure target of Cu (Z = 29). The angular distributions of relative intensity ratios were carried out by measuring the radiations emitted at incidence angle θi that varied from 15° to 75° in reflection geometry mode of the target. The x-rays emerging from the target surface were detected by an energy dispersive Si PIN photodiode detector. The magnitude of relative intensity ratio of Kα /BS is found to be larger than that of Kβ /BS by a factor of about 5.11, 5.24 and 5.49 for 15 keV, 20 keV and 25 keV impact energy, respectively measured, for example, at θi = 15°. However, the intensity ratio of a given characteristic line to its underneath BS increases on average by a factor of about 2.2 in varying the impact energy from 15 keV to 25 keV measured at different angles. The experimental results on angular and impact energy dependence are compared with the corresponding results obtained from Monte-Carlo simulations using the PENELOPE code. The overall agreement between experiment and theory is found to be satisfactory within the uncertainty of measurements. Highlights: Angular and impact energy dependence of intensity ratio of K x-rays to underneath BS radiation from 15 to 25 keV electrons incident on a thick Cu target is reported. Measured intensity ratios show good agreement with those calculated from PENELOPE. Relative magnitude of intensity ratio of Kα /BS is found to be much larger than that of Kβ /BS. The intensity ratios of Kα, β to respective underneath BS increases linearly with the impact energy of electrons.